Answer:
58 meters
Step-by-step explanation:
We are looking for the length of the base of a triangle, given the height and area. The formula for the area of a triangle
A=1/2 bh
relates A= the area, b= length of the base, and h= the height of a triangle, so this is the formula we should use.
We are given that the area of the triangle is A=493 and the height h=17. Substitute this information into the formula and solve for b to find
A=493
493=1/2⋅b⋅17
493=17/2b
58=b
The length of the base is 58 meters.
The length of the base of the triangle is 58 meters.
Given,
A triangular flag has an area of 493 square meters and a height of 17 meters.
We need to find what is the length of the base.
What is the area of a triangle?The area is given by:
= 1/2 x base x height
Find the area of the triangle.
Area = 493 square meters
Height = 17 meters
Area = 1/2 x base x height
493 square meters = 1/2 x base x 17 meters
Multiply 2 on both sides.
2 x 493 = 2 x 1/2 x base x 17
986 = base x 17
Dividing both sides by 17.
986 / 17 = base
Base = 58 meters.
Thus the length of the base of the triangle is 58 meters.
Learn more about finding the dimensions of triangles here:
https://brainly.com/question/15484541?referrer=searchResults
#SPJ2
the perimeter of a triangle below is 6a + 2b -5 units. write expression to represent the length in units , of the missing side of the triangle
2a-3b
a-3
As are know sides.
Anya found the slope of the line that passes through the points (–7, 4) and (2, –3). Her work is shown below. Let (x2, y2) be (–7, 4) and (x1, y1) be (2, –3). m = = = The slope is . What error did she make? She simplified the denominator incorrectly. The denominator simplifies to –7. She labeled the points incorrectly. The point (–7, 4) should be (x1, y1). She used an incorrect formula. The formula should be the change in y-values with respect to the change in the x-values. She used an incorrect formula. The formula should be the sum of the x-values with respect to the sum of the y-values.
Answer:
She used an incorrect formula. The formula should be the change in y-values with respect to the change in the x-values
Step-by-step explanation:
we know that
The formula to calculate the slope between two points is equal to
[tex]m=\frac{y2-y1}{x2-x1}[/tex]
we have
[tex](x2,y2)=(-7,4)[/tex]
[tex](x1,y1)=(2,-3)[/tex]
Substitute the values
[tex]m=\frac{4+3}{-7-2}[/tex]
[tex]m=\frac{7}{-9}[/tex]
[tex]m=-\frac{7}{9}[/tex]
therefore
She used an incorrect formula. The formula should be the change in y-values with respect to the change in the x-values
Answer:
C
Step-by-step explanation:
Write twenty billion,one million thirty thousand and one as a number
Answer:
20,001,030,001
For this case we must express the following phrase in numerical form:
"twenty billion, one million thirty thousand and one as a number"
twenty billion is equivalent to [tex]20,000,000,000[/tex]
one million equals [tex]1,000,000[/tex]
thirty thousand equals [tex]30,000[/tex]
one equals 1
Then, we can express:
[tex]20,001,030,001[/tex]
Answer:
20,001,030,001
Rewrite without parentheses and simplify.
(6w+7)
Answer:
6w + 7
Step-by-step explanation:
There is nothing to simplify. Just remove the parentheses.
–42 ÷ (–6) a.–252 b.–7 c. 7 d. 252
Answer:
a negative multiplied or divided by negative is positive. if its adding or subtracting it takes sign of the bigger number. and it dividing so the number is not going to get bigger. so its positive 7
[tex]\text{Hey there!}[/tex]
[tex]\text{Since, both of your terms (-42 and -6) are negative, we know that your answer}[/tex] [tex]\text{will most likely be a POSITIVE number}[/tex]
[tex]\text{Because. negative \& negative makes positive!}[/tex]
[tex]\text{-42}\div\text{(-6)}=\dfrac{-42}{(-6)}=42\div6=7[/tex]
[tex]\boxed{\boxed{\text{Answer: C. 7}}}\checkmark[/tex]
[tex]\text{Good luck on your assignment and enjoy your day!}[/tex]
~[tex]\frak{LoveYourselfFirst:)}[/tex]
Is abc~def? If so, identify the similarity postulate or theorem that applies.
Answer:
Similarity cannot be determined ⇒ answer D
Step-by-step explanation:
* Lets revise the cases of similarity
1) AAA similarity : two triangles are similar if all three angles in the first
triangle equal the corresponding angle in the second triangle
- Example : In ΔABC and ΔDEF, m∠A = m∠D, m∠B = m∠E and
m∠C= m∠F then ΔABC ≈ ΔDEF by AAA
2) AA similarity : If two angles of one triangle are equal to the
corresponding angles of the other triangle, then the two triangles
are similar.
- Example : In ΔPQR and ΔDEF, m∠P = m∠D, m∠R = m∠F then
ΔPQR ≈ ΔDEF by AA
3) SSS similarity : If the corresponding sides of two triangles are
proportional, then the two triangles are similar.
- Example : In ΔXYZ and ΔLMN, if [tex]\frac{XY}{LM}=\frac{YZ}{MN}=\frac{XZ}{LN}[/tex]
then the two triangles are similar by SSS
4) SAS similarity : In two triangles, if two sets of corresponding sides
are proportional and the included angles are equal then the two
triangles are similar.
- Example : In triangle ABC and DEF, if m∠A = m∠D and [tex]\frac{BA}{ED}=\frac{CA}{FD}[/tex]
then the two triangles are similar by SAS
* Now lets solve the problem
- In the triangles ABC and DEF
∵ m∠B = m∠E = 105°
∵ AB/DE = 16/4 = 4
∵ AC/DF = 36/9 = 4
∴ AB/DE = AC/DF = 4
∴ The two pairs of sides are proportion
∵ ∠B and ∠E are not the including angles between the sides AB , AC
and DE , DF
∵ We could not find the including angles from the information of the
problem
∴ We cannot prove the similarity
* Similarity cannot be determined
Answer:
D- can't be determined
Step-by-step explanation:
a p e x work
The value of k so that the sequence k-1, k+3, 3k-1 forms an arithmetic progression is?
Answer:
k = 4.
Step-by-step explanation:
An arithmetic sequence has a common difference.
So for this to be arithmetic:
k + 3 - (k - 1) = 3k - 1 - (k + 3)
k + 3 - k + 1 = 3k - 1 - k - 3
3 + 1 = 2k - 4
4 + 4 = 2k
k = 4.
The sequence is 3, 7, 11.
Which pair of spheres are congruent?
R and S
R and T
S and T
Answer:
S and T
Step-by-step explanation:
I put R&T, that's wrong. It's S and T.
The pair of spheres are congruent is S and T.
What is congruence?Two figures or objects are congruent if they have the same shape and size, or if one has the same shape and size as the mirror image of the other.
As, per the given figure,
Figure R having a radius 3.
Figure S is having a radius 4
Figure T is having radius 4
So, by considering the property of congruence figure S and T will be congruent spheres.
Learn more about congruence here:
brainly.com/question/7888063
#SPJ2
please!!!!! ANSWERR!! HURRY ILL MARK YOU AS BRAINNN
Answer:
A=280in^2
Step-by-step explanation:
3*3=9
A=2LW+2WH+2LH
A=2(8*4)+2(4*9)+2(8*9)
A=2(32)+2(36)+2(72)
A=64+72+144
A=280in^2
The Eagle Club wants to build a chain of 2,505 dominoes. If they have already set up 807 dominoes, how many more do they need to add to meet their goal?
Answer:
1698
Step-by-step explanation:
Answer:
They would need 1698 dominoes to complete the chain.
Step-by-step explanation:
all you would do is subtract 2,505 by 807 and you would get the same answer.
Help me I need to pass so I can go on to the next thing plz someone help me
Answer:
The scale factor is 2
Step-by-step explanation:
AB -->A'B' : enlargement , scale factor is greater than 1
From QA to QA' : 1.25 to 2.5 so the ratio is 1:2
The scale factor is 2
Pls help. Ignore the orange around one of the choices.
The temperature started at -12 degrees then increases by 8 degrees. This means that you can make an expression to solve this like so...
-12 + 8
When adding a positive number with a negative number you will act as if you are subtracting the two numbers, then take the sign of the largest number. In this case the largest number is 12 and its sign is negative. Your answer will have a negative sign.
Act as if you are subtracting...
12 - 8 = 4
Take the sign of the largest number (12)
-4 (third option)<<<This is the temperature now.
Hope this helped!
~Just a girl in love with Shawn Mendes
Answer:
-4F
Step-by-step explanation:
We start at -12
We rise 8
-12 +8
-4
We will then be at -4
take 25% off the original. now take off an additional 10% and calculate the new sales cost of this item. what is your total percent of savings?
x = original price, or 100%
if we take off 25% from 100% what's left is 75%, that's the discounted price.
let's then take 10% of that.
[tex]\bf \begin{array}{|c|ll} \cline{1-1} \textit{a\% of b}\\ \cline{1-1} \\ \left( \cfrac{a}{100} \right)\cdot b \\\\ \cline{1-1} \end{array}~\hspace{5em}\stackrel{\textit{75\% of "x"}}{\left( \cfrac{75}{100} \right)x\implies 0.75x} \\\\[-0.35em] ~\dotfill\\\\ \stackrel{\textit{10\% of 0.75x}}{\left( \cfrac{10}{100} \right)0.75x\implies 0.075x}~\hfill \stackrel{\textit{total percent savings}}{0.75x-0.075x\implies 0.675x} \\\\[-0.35em] ~\dotfill[/tex]
[tex]\bf \stackrel{\textit{changing that to percent format}}{0.675\cdot 100\implies 67.5\%}[/tex]
In the game of blackjack played with one deck, a player is initially dealt 2 different cards from the 52 different cards in the deck. A winning "blackjack" hand is won by getting 1 of the 4 aces and 1 of 16 other cards worth 10 points. The two cards can be in any order. Find the probability of being dealt a blackjack hand. What approximate percentage of hands are winning blackjack hands?
Answer:
[tex]P =4.83\%[/tex]
Step-by-step explanation:
First we calculate the number of possible ways to select 2 cards an ace and a card of 10 points.
There are 4 ace in the deck
There are 16 cards of 10 points in the deck
To make this calculation we use the formula of combinations
[tex]nCr=\frac{n!}{r!(n-r)!}[/tex]
Where n is the total number of letters and r are chosen from them
The number of ways to choose 1 As is:
[tex]4C1 = 4[/tex]
The number of ways to choose a 10-point letter is:
[tex]16C1 = 16[/tex]
Therefore, the number of ways to choose an Ace and a 10-point card is:
[tex]4C1 * 16C1 = 4 * 16 = 64[/tex]
Now the number of ways to choose any 2 cards from a deck of 52 cards is:
[tex]52C2 =\frac{52!}{2!(52-2)!}[/tex]
[tex]52C2 = 1326[/tex]
Therefore, the probability of obtaining an "blackjack" is:
[tex]P = \frac{4C1 * 16C1}{52C2}[/tex]
[tex]P = \frac{64}{1326}[/tex]
[tex]P = \frac{32}{663}[/tex]
[tex]P =0.0483[/tex]
[tex]P =4.83\%[/tex]
Answer:
Probability = 0.0483
Percentage = 4.83%
Step-by-step explanation:
We know that a blackjack hand played with one deck consists of:
1 of the 4 aces = [tex]\frac{4}{52}[/tex]
So 1 out of the 16 cards worth 10 points will be equal to = [tex]\frac{16}{52}[/tex]
Finding the probability of getting a blackjack hand assuming that the cards were not replaced:
P (blackjack hand) = P(1st ace) × P(2nd 10 point card) + P(1st 10 point card) × P(2nd ace)
P (blackjack hand) = [tex]\frac{4}{52} \times \frac{16}{51} + \frac{16}{52} \times \frac{4}{51}[/tex] = 0.04827
Percentage of getting blackjack hand = 4.83%
Multiply.
(x2 - 5x)(2x + x-3)
Hi there! My name is Zalgo and I am here to help you out today. When you multiply (x2-5x) (2x+x-3), you will get 3x^3-18x^2+15x.
I hope that this info helps! :)
"Stay Brainly and stay proud!" - Zalgo
(By the way, can you mark me Brainliest? I'd greatly appreciate it! Thank you! XP)
In order to solve for the variable in the equation Mikel first applies the distributive property. Which equation is a result of this step?
Answer:
1 - x - 2 + 2x = 10x - 25 - x
Step-by-step explanation:
We have the expression: 1 - (x+2) + 2x = 5(2x - 5) - x
Applying the distributive property we get:
1 - x - 2 + 2x = 10x - 25 - x
So, the following equation is the result of that step: 1 - x - 2 + 2x = 10x - 25 - x
Answer:
The equation is:
[tex]1-x-2 + 2x = 10x-25-x[/tex]
Step-by-step explanation:
The distributive property says that
[tex]c(a+b) = ac + bc[/tex]
In this case we have the following equation
[tex]1-(x+2) + 2x = 5(2x-5)-x[/tex]
Then apply the distributive property as shown below
[tex]1-1*x-1*2 + 2x = 5*2x-5*5-x[/tex]
Now simplify the expression
[tex]1-x-2 + 2x = 10x-25-x[/tex]
So the equation that results after applying the distributive property is:
[tex]1-x-2 + 2x = 10x-25-x[/tex]
Which pair of lines is parallel? A. y=4x+1 and y+4=5 B. y=-2+x and 2y-2x=-2 C. y=1/4x + 2 and y-2=1/2x D. y=1/5x+1 and 5y+x= 10
Answer:
B. y=-2+x and 2y-2x=-2
Step-by-step explanation:
Two lines are parallel if they have the same slope.
The equation 0of a line is tipically written as y=mx + b, where 'm' represents the slope and 'b' the y-intercept.
Let's evaluate each of the options:
A. y=4x+1 and y+4x=5
Writing the equations in the slope-intercept form, we get:
y=4x+1 → m=4
y=5-4x → m=-4
Given that they have different slopes, they are not parallel.
B. y=-2+x and 2y-2x=-2
Writing the equations in the slope-intercept form, we get:
y=-2+x → m=1
y=-1 + x → m=1
Given that the equations have the same slope, they are parallel.
C. y=1/4x + 2 and y-2=1/2x
Writing the equations in the slope-intercept form, we get:
y=1/4x + 2 → m=1/4
y=1/2x+2 → m=1/2
Given that they have different slopes, they are not parallel.
D. y=1/5x+1 and 5y+x= 10
Writing the equations in the slope-intercept form, we get:
y=1/5x+1 → m=1/5
5y+x= 10 → y=2 - 1/5x → m=-1/5
Given that they have different slopes, they are not parallel.
will 5x-3y>15 have a solid line
Answer:
The inequality [tex]5x-3y >15[/tex] have a dashed line
Step-by-step explanation:
we have
[tex]5x-3y >15[/tex]
The solution of this inequality is the shaded area below the dashed line
The equation of the dashed line is [tex]5x-3y=15[/tex]
The slope of the dashed line is positive
The y-intercept of the dashed line is -5 ---> point (0,-5)
The x-intercept of the dashed line is x=3 ----> point (3,0)
Graph the solution
see the attached figure
please help
1. f(x)=3(2)^x
2. f(x)=2(3)^x
3. f(x)=3(1/2)^x
4. f(x)=2(1/3)^x
Answer:
C. f(x)=3(1/2)^x
Step-by-step explanation:
standard form of a function is f(x)=ab^x
a should be 3, or the y value where the x value is 0
the b value is 1/2 because that's the rate of change
Find measure jk
Answers are 52, 128, 154 & 180
Answer:
b. 128°
Step-by-step explanation:
arc LJ = 2 (26) = 52°
arc KL = 180° (half circle)
so
arc JK = 360° - (arc LJ + arc KL)
arc JK = 360° - 232°
arc JK = 128°
Answer
b. 128°
The difference between three times a number and seven is twenty. What is the number?
Answer:
9
Step-by-step explanation:
(9*3) = 27 which is 20 more than 7
Answer: 9
Step-by-step explanation:
Add -4/y + (-7/8y).
please help
Answer:
-39/8y
Step-by-step explanation:
-4/y(2)+(-7/8y)
A truck can be rented from company A for $40 a day plus $0.30 per mile. Company B charges $20 a day plus $0.70 per mile to rent the same truck. Find the number of miles in a day at which the rental costs for company A and company B are the same.
Despite different rental costs, the rental costs for company A and company B will be the same, after 50 miles.
To solve this, we need to set up an equation based on their pricing structures and solve for the number of miles.
Let m represent the number of miles driven. The cost for company A would be $40 + $0.30m, and the cost for company B would be $20 + $0.70m.
We set these two expressions equal to each other to find the breakeven point:
$40 + $0.30m = $20 + $0.70m
Subtracting $0.30m from both sides gives us:
$40 = $20 + $0.40m
Next, we subtract $20 from both sides:
$20 = $0.40m
Dividing both sides by $0.40, we get:
m = 50
What is the length of the hypotenuse of the triangle?
Answer:
8.1 ft
Step-by-step explanation:
hyp² = side² + side²
hyp² = 7² + 4²
hyp² = 49 + 16
hyp² = 65
hyp = sqrt of 65
hyp = 8.1 ft
PLEASE DO MARK ME AS BRAINLIEST UWU
Answer:
[tex]\large\boxed{\sqrt{65}\ ft}[/tex]
Step-by-step explanation:
Use the Pythagorean theorem:
[tex]leg^2+leg^2=hypotenuse^2[/tex]
We have
[tex]leg=4ft,\ leg=7ft,\ hypotenuse=AB[/tex]
Substitute:
[tex]AB^2=4^2+7^2\\\\AB^2=16+49\\\\AB^2=65\to AB=\sqrt{65}[/tex]
What is the value of x in the equation 3x -1/9
y = 18, when y = 27?
5
7
45 63
Answer:
[tex]x=7[/tex]
Step-by-step explanation:
we have
[tex]3x-\frac{1}{9}y=18[/tex]
Substitute the value of y=27 in the equation and find the value of x
so
[tex]3x-\frac{1}{9}(27)=18[/tex]
[tex]3x-3=18[/tex]
[tex]3x=18+3[/tex]
[tex]3x=21[/tex]
[tex]x=7[/tex]
Austin has $80 in a savings account. The interest rate is 5%, compounded annually. To the nearest cent, how much will he have in 2 years?
PLS HELP OMG
-
what is the best estimate of a 20% tip if you ordered a meal that cost $29.35?
Answer:
5.87
Step-by-step explanation:
29.35/x=100/20
(29.35/x)*x=(100/20)*x - we multiply both sides of the equation by x
29.35=5*x - we divide both sides of the equation by (5) to get x
29.35/5=x
5.87=x
x=5.87
Answer:
$5.87
Step-by-step explanation:
20% = 20/100 = 1/5
hence 20% tip,
= 20% of the total cost
= 1/5 x $29.35
= $5.87
Which word best describes the range of a function? input output independent relation
Answer:
Output
Step-by-step explanation:
A function takes values of x (the horizontal axis on a plane)and returns the corresponding values of y (the vertical axis on a plane).
Thus, the values we get for y depends on the value of x.
The x's values that we give in a function are called the domain, and the values that the function returns to us are called the range of the function (the y's).
So a word that describes the range of a function well is that the range is the output of the function. Because the range is the set of values that the function returns to us when we plug an x value.
2 and 3 are
angles.
complementary
vertical
congruent
supplementary
Answer:
supplementary
Step-by-step explanation:
Angles 2 and 3 form a straight line. Straight lines are supplementary
Answer:
Supplementary
Step-by-step explanation:
1 and 2 are vertical along with 3 and 4 they can't be complementary non of them form right angles but supplementary is a straight line making 180 degrees.
x + y = k
2x + 3y = k + 1
The point of intersection of the lines has an x-coordinate of
A.2k + 1
B.-2k + 1
C.2k - 1
Answer: Yes A is correct
Step-by-step explanation:
Multiply the first equation by 3...
2x+3y=k+1 needs to be subtracted by 3x+3y=3k
which equals -x=-2k-1
Then you can multiply the equation by -1 to make them all positive. Resulting in x=2k+1
The correct option is c.
To solve the given simultaneous linear equations x + y = k and 2x + 3y = k + 1 using the elimination method, multiply the equations by suitable constants to eliminate one variable. The values of x and y in terms of k are x = 2k - 1 and y = 1 - k.
Explanation:To solve the given simultaneous linear equations x + y = k and 2x + 3y = k + 1 using the elimination method, we can eliminate one variable by multiplying the equations by suitable constants. Let's multiply the first equation by 2 and the second equation by -1 to eliminate x.
2x + 2y = 2k
-2x - 3y = -k - 1
Adding these equations together, we get:
2y - 3y = 2k - (k + 1)
-y = k - 1
Multiplying both sides by -1:
y = 1 - k
Substituting this value of y back into the first equation:
x + (1 - k) = k
x = 2k - 1
So, the values of x and y in terms of k are x = 2k - 1 and y = 1 - k.
Learn more about Solving simultaneous linear equations here:https://brainly.com/question/34495857
#SPJ3